2021
DOI: 10.1088/1755-1315/906/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Geology of Zagros metamorphosed volcaniclastic sandstones: a key for changing the Mawat Ophiolite Complex to a metamorphic core complex, Kurdistan Region, NE-Iraq

Abstract: Mawat Ophiolite Complex is located about 36 km to the northeast of Sulaimani city and directly to the east-northeast of Mawat town near the border of Iran in the northeastern Iraq. The complex has about 600-km2 surface area and consists of high mountain terrains that subjected to intense geological investigations from the fiftieth of previous century till now. According to previous studies, the complex contains tens of igneous rocks such as basalt, metabasalt, tuff, diabase, metadiabase, diorite dykes, periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This tectonic feature is called Mawat Nappe by [5] who showed its thrusting over the Red Bed Series and Cretaceous rocks. In contrast to the Ophiolites Complex ideas of the previous authors such as [29,30] changed the area to the metamorphic core complex of a sedimentary origin.…”
Section: Geological Setting Of the Areamentioning
confidence: 86%
“…This tectonic feature is called Mawat Nappe by [5] who showed its thrusting over the Red Bed Series and Cretaceous rocks. In contrast to the Ophiolites Complex ideas of the previous authors such as [29,30] changed the area to the metamorphic core complex of a sedimentary origin.…”
Section: Geological Setting Of the Areamentioning
confidence: 86%
“…Karim and Abioui (2021) [26] found a similar conglomerate in several places on Avroman Mountain between Qulqula and Avroman Formations and directly on the conglomerate of the Tanjero Formation. Karim and Ghafur (2021) [27] recorded the same type of conglomerate inside the Walash Formation (group) 100 m above the Shiranish Formation in the Mawat area (1 km south of the Gabra village). Many claimed felsic dykes (granitoid or dioritic dykes) are recorded by [28], Abdulzahra and Hadi (2017) [29], and Abdulzahra, et al ( 2019) [23] in and around the Kata Rash group (present conglomerate) but when inspected in the present study; their presence as a dyke is not proved since they cut nothing and not associated with mineralization, contact metamorphism, and digitation into country rocks.…”
Section: Kata Rash Volcanic Rock Groupmentioning
confidence: 86%
“…In rare cases, the mafic volcanoclastic sandstones (greywackes) are so intensely pulverized and sheared that transformed into massive and amalgamated bodies which are previously called serpentinite in which serpentinization and shearing are observable even on a millimetric scale, especially on the southwestern boundary of the Penjween Ophiolite Complex (present metamorphosed greywackes) on the Milakawa Mountain at 1km north of Kani Manga village. As concerned to the other ophiolites and volcanic rocks outside the Penjween area in northern Iraq, Karim and Al-Bidry (2020) [34], Karim et al (2020) [35], Karim and Abioui (2021) [26], and Karim and Ghafur (2021) [27] studied many of them objectively and amended them to sedimentary successions. In these successions, the latter studies found ten of evidence confirming their new sedimentary origin.…”
Section: Penjween Ophiolite Complexmentioning
confidence: 99%
“…As an example: a rock sample is very difficult to be proved as a meteorite by the geochemical analysis while boundary conditions and outline features can be more decisive. Therefore, if the sample was strange in its area of occurrence and has signs of burnt outlines, they reveal most possibly a meteorite Karim et al (2020) [29], Karim (2021) [45] and Karim and Abioui, (2021) [27] clarified the inability of textures and geochemistry to indicate the origin of rocks. These latter three articles presented more than ten pieces of evidence for refuting the magmatic origin of the Mawat Ophiolite, Avroman and Gercus basaltic bodies in northern Iraq.…”
Section: The Problem Of the Absence Of The Present-day Ophiolite Obdu...mentioning
confidence: 99%
“…We think that the regional metamorphism affected the rocks of the latter three complexes and changed the Penjween, Mawat and Bulfat to amphibolite and greenschist facies. Karim and Al-Bidry (2020) [23] and Karim and Abioui (2021) [27] and Karim (2021) [45] discussed tens of signals of sedimentary origins of these claimed ophiolite complexes. The rocks of these complexes consist of alternations of thousands of layers of different rocks such as pure limestone, clayey limestone, sandy limestone, marls, shales, calcareous shales, volcanic detritus, greywackes, arkose, arenites (plagioclase, olivine, amphibole or pyroxene arenites).…”
Section: Absence Of Contact Metamorphism Between Igneous and Host Roc...mentioning
confidence: 99%